Experimental Investigation of the Effect of Pack Carburization on Impact Strength and Hardness Property of ASTM A516/516M-05 Steel Plate Weldment - Oreko, Benjamin Ufuoma; B. Otanocha, Omonigho; Idi, Stanley (International Journal of Integrated Engineering, 2020)
This study investigates the effect of pack carburization on hardness property of ASTM A516/516M-05 steel plate weldment. Sixteen (16) samples were structured, prepared and machined into twelve (12) and four (4) for impact and Vickers hardness tests, respectively. Eight (8) samples were carburized at a constant temperature of 920oC, withholding time of 15 minutes and the other eight (8) samples act as a control. The result obtained shows that the welded and heat treated (WHT) sample has the highest impact strength with an average impact value of 218 J, closely follow by the non-welded but heat treated (NWHT) sample with an average impact strength of 198 J. The Welded but not heated treated (WNHT) sample has an average impact test of 176 J while the non-welded non-heat treated (NWNHT) recorded a value of 168 J. Also, the Vickers hardness result shows that the welded and heat treated, non-welded but heat treated and the non-welded non-heat treated samples have an average hardness numbers of 218, 213.7 and 181.4, respectively. Also, the hardness values were uniformly distributed across the surface layers of the steel.  However, for the welded but not heat treated samples, it has a hardness number of 193.9 with an appreciable variation of hardness value from the fusion zone to the heat affected zone (HAZ) and the parent metal. It was observed that carburization of ASTM A516/516M-05 steel increases the hardness and impact strength of the material.